2018
DOI: 10.1007/s11095-017-2281-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Moisture-Induced Crystallization on the Aerosol Performance of Spray Dried Amorphous Ciprofloxacin Powder Formulations

Abstract: This study provides a fundamental understanding in moisture-induced physical and aerosol instability of the spray dried powder formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…However, they have around 50-60% FPF results due to the apparent high cohesive properties between the active ingredient's particles [26,27]. Many publications deal with the development of DPI containing ciprofloxacin or ciprofloxacin hydrochloride [12,[28][29][30][31][32][33]. A serious challenge of our previous work was using the benefits of these two formulations (applying 1:10 ratio and current inhaled antibiotics are $100 mg), the novel combined formulation (a co-spray-dried drug blended with surface modified lactose) produced by us resulted in a higher FPF value than the carrier-based and carrier-free DPI formulations [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, they have around 50-60% FPF results due to the apparent high cohesive properties between the active ingredient's particles [26,27]. Many publications deal with the development of DPI containing ciprofloxacin or ciprofloxacin hydrochloride [12,[28][29][30][31][32][33]. A serious challenge of our previous work was using the benefits of these two formulations (applying 1:10 ratio and current inhaled antibiotics are $100 mg), the novel combined formulation (a co-spray-dried drug blended with surface modified lactose) produced by us resulted in a higher FPF value than the carrier-based and carrier-free DPI formulations [18].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant capsules were used in a low-resistance RS01 DPI device (similar design to Osmohaler, Plastiape S.p.A., Osnago, Italy), with 4 L of air passing through the inhaler at an airflow of 100 L/min for 2.4 s, with a pressure drop of approximately 4 kPa (39). Drugs retained in the capsule, inhaler device, USP throat and Stage 1–8 of the impactor were collected using 20 mL of a co-solvent consisting of 1:1 v/v of 20 mM potassium dihydrogen phosphate (adjusted to pH 5 with 10 % w/v sodium hydroxide) and methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the spray-dried ciprofloxacin is amorphous, which tends to crystallize upon storage and affects the aerosolization. 12 Because the jet-milled ciprofloxacin was crystalline, it is likely to have better physical stability than the spray-dried amorphous ciprofloxacin particles.…”
Section: Powder X-ray Diffractionmentioning
confidence: 99%
“…The unstable amorphous particles may convert into more thermodynamically stable crystalline form, 11 which could alter the aerosolization behavior. [12][13][14] Although the jet-milled particles are in general very cohesive with poor flowability and unsatisfactory aerosolization behavior, 15,16 jet milling is still the mainstay approach to manufacture inhalable drug particles in the industrial practice. 7 Studies have also shown that co-jet milling with lubricants may potentially facilitate simultaneous particle size reduction and particle surface coating, which resulted in improved aerosolization performance.…”
Section: Introductionmentioning
confidence: 99%